The Synthesis of Methyl Ester Nitrate from Ketapang Seed Oil (Terminalia catappa L.) - Nurliana, Laily; Ritonga, Halimahtussaddiyah; Feronika, Yulita; Musta, Rustam (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The synthesis of methyl ester nitrate (MEN) from ketapang oil (Terminalia catappa L.) have been carried out. This study aims to determine the yield and the characteristics of MEN. In this study, ketapang seed oil was obtained from the soxhlet extraction process followed by an evaporation process to separate the oil from the solvent. MEN can be produced from ketapang seed oil by esterification to convert all of FFA became ester, followed by transesterification that intended to produce ester from triglycerides and nitrationthat is reaction of esther and HNO3 to create MEN. Evaporated oil is esterified using methanol with a mole ratio of oil: methanol (1: 6), then the transesterification process using methanol with a mole ratio (1:15) gives a yield of 86%. The transesterification product was then nitrated using HNO3 and H2SO4 for 4 hours with a yield of 83%. Characterization of methyl ester using GC-MS characterization showed the presence of methyl palmitoleate (C17H32O2), methyl palmitate (C19H34O2), methyl oleate (C19H36O2), methyl 13-octadecanoic (C19H36O2), methyl stearate (C19H38O2), and methyl 18-nonadecanoic (C21H42O2). Characterization MEN using a FTIR spectrophotometer showed the presence of a C-ONO2 group at wave number 1550 cm-1, NO2 group at wave number 1365 cm-1 and a C-N group at wave number 1118 cm-1. It shows that MEN can be synthesized from ketapang seed oil.